2020
DOI: 10.1038/s41598-020-59842-2
|View full text |Cite|
|
Sign up to set email alerts
|

Noninvasive imaging of vascular permeability to predict the risk of rupture in abdominal aortic aneurysms using an albumin-binding probe

Abstract: Abdominal aortic aneurysm (AAA) remains a fatal disease. its development encompasses a complex interplay between hemodynamic stimuli on and changes in the arterial wall. currently available biomarkers fail to predict the risk of AAA rupture independent of aneurysm size. therefore, novel biomarkers for AAA characterization are needed. in this study, we used a mouse model of AAA to investigate the potential of magnetic resonance imaging (MRi) with an albumin-binding probe to assess changes in vascular permeabili… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…For AAA, similar findings could apply. Our findings from a previous study on AAA using an albumin-binding probe already suggested an increased vascular permeability in murine AAA 25 . Another benefit in molecular imaging studies could be obtained by using quantitative MRI protocols, which would not only allow to visualize, but also to quantify the molecular probes used.…”
Section: Discussionsupporting
confidence: 64%
“…For AAA, similar findings could apply. Our findings from a previous study on AAA using an albumin-binding probe already suggested an increased vascular permeability in murine AAA 25 . Another benefit in molecular imaging studies could be obtained by using quantitative MRI protocols, which would not only allow to visualize, but also to quantify the molecular probes used.…”
Section: Discussionsupporting
confidence: 64%
“…As an albumin-binding extracellular contrast agent, gadofosveset showed a strong signal in the disrupted areas of the aneurysm wall in all animals, which could be quantified by CNR. e protective effect in the doxycycline group was shown, as expected, by a significantly reduced CNR in the gadofosveset-enhanced MR angiography compared to the untreated control group from the previous study [21]. is could be interpreted as a sign of reduced endothelial damage in this group and thus reduced leakage of albumin and consecutively gadofosveset into the aneurysm wall.…”
Section: Discussionsupporting
confidence: 76%
“…Noninvasive imaging techniques such as magnetic resonance imaging have already been successfully used to evaluate structural components of AAA and potential rupture risks in a mouse model [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…LA-ICP-MS was performed for quantitative elemental imaging of Gd, Fe, Zn, and P as described previously 43 , 44 . To determine the gadolinium distribution within the periablational rim following the injection of the elastin-specific gadolinium-based agent, x-ray spectra were acquired in the gadolinium distribution and the gadolinium distribution was mapped.…”
Section: Methodsmentioning
confidence: 99%